An 8 GHz real-time temperature-compensated PLL with 20.8 ppm/°C temperature coefficient for SerDes applications. (November 2021) - Ding, Li; Wu, Ke; Jin, Jing; Zhou, Jianjun
Abstract: A real-time temperature-adaptive phase-locked loop (PLL) is proposed in this brief. To prevent the PLL from going out of lock due to significant temperature variation, a temperature-compensated loop based on the idle circuits of automatic amplitude control (AAC) is designed, which senses temperature variation by detecting the changes of output amplitude. The PLL output frequency is then adjusted by controlling the temperature-compensated varactor of the voltage-controlled oscillator. The proposed PLL is fabricated in a 22 nm silicon on insulator (SOI) process, which covers 0.27 mm2 of the chip area. The temperature-compensated loop dissipates only 40 uA under 0.9 V supply voltage while the overall PLL consumption is 10 mA. The tuning voltage of VCO can be controlled within 200 mV, while PLL maintains locked in the ambient temperature range from −40 °C to 170 °C.